055 Effect of common concomitant antiepileptic drugs during adjunctive treatment with perampanel: post hoc analysis from the open-label extension of a phase III study in patients with idiopathic generalised epilepsy. Issue 6 (24th May 2018) - O'Brien, Terence J; Bibbiani, Francesco; Patten, Anna; Laurenza, Antonio; Williams, Betsy
Abstract : Introduction: Perampanel is approved for adjunctive treatment of partial seizures, with or without secondarily generalised seizures, and primary generalised tonic-clonic (PGTC) seizures in epilepsy patients aged ≥12 years. Perampanel is also approved for monotherapy use for partial seizures in the US. This post hoc analysis assessed the effects of the most common concomitant Baseline antiepileptic drugs (AEDs) on discontinuation rates and treatment-emergent adverse event (TEAE) incidence during adjunctive treatment with perampanel in patients (aged ≥12 years) with idiopathic generalised epilepsy (IGE) and PGTC seizures in the open-label extension (OLEx) Phase of Study 332 (NCT02307578 ). Methods: Patients completing the double-blind study could receive perampanel (≤12 mg/day) during the OLEx (6 week blinded Conversion Period;≤136 weeks' Maintenance). Here, we report results for perampanel >4–8 mg/day and >8–12 mg/day. Results: Most common concomitant Baseline AEDs were valproic acid (n=55), lamotrigine (n=53), levetiracetam (n=37), topiramate (n=21) and zonisamide (n=12); patients may have received >1 of these Baseline AEDs. The most common reasons for discontinuing were adverse event(s) (AE), 'other' and patient choice. Lamotrigine: patient choice, n=6/34 (>4–8 mg/day); AE/'other', both n=3/19 (>8–12 mg/day). Levetiracetam: patient choice, n=5/27 (>4–8 mg/day); AE, n=2/10 (>8–12 mg/day). Topiramate: 'other', n=3/15 (>4–8 mg/day); AE/'other', both n=1/6 (>8–12 mg/day). Valproic acid: patient choice, n=6/38 (>4–8 mg/day); 'other', n=4/17 (>8–12 mg/day). Zonisamide: patient choice/'other', both n=2/10 (>4–8 mg/day); no discontinuations (>8–12 mg/day). Patient-reported TEAEs ranged from: 88.2% (lamotrigine) to 93.3% (topiramate) for perampanel >4–8 mg/day, and 70.6% (valproic acid) to 100.0% (topiramate and zonisamide) for perampanel >8–12 mg/day. The most common TEAE was dizziness. Conclusion: In this post hoc analysis, primary reasons for discontinuation and TEAE incidence differed between the most common Baseline AED subgroups and perampanel dose range, although TEAE types were similar. These data provide additional information on the safety of adjunctive perampanel in patients with IGE. Study support: Eisai Inc.